2019
DOI: 10.1152/ajpheart.00106.2018
|View full text |Cite
|
Sign up to set email alerts
|

TRPA1 channel contributes to myocardial ischemia-reperfusion injury

Abstract: Myocardial ischemia-reperfusion (I/R) results in the generation of free radicals, accumulation of lipid peroxidation-derived unsaturated aldehydes, variable angina (pain), and infarction. The transient receptor potential ankyrin 1 (TRPA1) mediates pain signaling and is activated by unsaturated aldehydes, including acrolein and 4-hydroxynonenal. The contribution of TRPA1 (a Ca2+-permeable channel) to I/R-induced myocardial injury is unknown. We tested the hypothesis that cardiac TRPA1 confers myocyte sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 43 publications
2
40
0
Order By: Relevance
“…Furthermore, ROS-sensitive TRPA1 channel was found to contribute to Ca 2+ overload and hypercontraction of cardiomyocytes. Genetic ablation of TRPA1 caused a significant decrease in myocardial infarction after I/R in mice, indicating that I/R activation of TRPA1 worsens myocardial infarction [ 149 ]. In addition to channels in the plasma membrane, Ca 2+ transport proteins in ER and mitochondria are also crucial contributors to the development of cardiovascular diseases.…”
Section: Crosstalk Between Ros and Ca 2+ In Age-rementioning
confidence: 99%
“…Furthermore, ROS-sensitive TRPA1 channel was found to contribute to Ca 2+ overload and hypercontraction of cardiomyocytes. Genetic ablation of TRPA1 caused a significant decrease in myocardial infarction after I/R in mice, indicating that I/R activation of TRPA1 worsens myocardial infarction [ 149 ]. In addition to channels in the plasma membrane, Ca 2+ transport proteins in ER and mitochondria are also crucial contributors to the development of cardiovascular diseases.…”
Section: Crosstalk Between Ros and Ca 2+ In Age-rementioning
confidence: 99%
“…TRPA1 is present in cardiomyocytes and is important in regulating myocardial reperfusion injury ( Lu et al, 2016 ). A study showed that TRPA1 gene-knockout myocardial ischemia–reperfusion mice alleviated myocardial injury, indicating that TRPA1 channel activation mediates myocardial ischemia–reperfusion injury ( Conklin et al, 2019 ). This may be related to the accumulation of free radicals and unsaturated aldehydes generated after myocardial ischemia and reperfusion to activate TRPA1 channel.…”
Section: Trpa1 and Common Cardiovascular Diseasesmentioning
confidence: 99%
“…This is especially true for diseases in which additional factors that activate TRPA1 channels are present (e.g., oxidative stress 36 ), as the response of TRPA1 channels to mechanical stimulation is enhanced by an increase in its baseline activity 9 . For instance, acute myocardial ischemia resulting from blockage of a / 35 coronary artery is associated with TRPA1-mediated myocardial damage 13 and lethal ventricular arrhythmias that are thought to involve contributions of altered tissue mechanics, intracellular Ca 2+ handling, and oxidative stress 37 , so targeting TRPA1 channels in that setting could help prevent multiple detrimental outcomes (and perhaps even promote post-ischemic myocardial repair 14 ).…”
Section: / 35mentioning
confidence: 99%